Improving Educational Learning Outcomes Citizenship Through Strategy Active Learning - Hakiki, Muthia (International Journal of Students Education, 2024)
This study aims to determine the improvement in learning outcomes after the implementation of active learning in the civic education course at Muhammadiyah University North Sumatra. Study this is study using the Literature Review method through two cycles, every cycle consists of the stages of planning, implementation, observation, and reflection. The subjects of this study were student class A2 semester 2 Primary School Teacher Education University Muhammadiyah of North Sumatra year teachings 2015/2016 totaling 36 students, 3 male students and 33 female students. The research results show that there is an increase in the completion of students' lecture results. with cycle I completion reaching 72% (26 students) increasing in cycle II to 86% (31 students). Based on this, it can be concluded that the implementation of the active strategy learning can increase results Study student on eye studying education citizenship.